Gluten free diet does not alter diabetic control in children with "silent" celiac disease - Manoj K Ghoda; Atit Ghoda (Archives of Hepatitis Research - Peertechz Publications, 2020)
Celiac disease which is an autoimmune enteropathy has a well recognized association with type I diabetes in about 3.5 to 10% of patients [1]. Routine screening for celiac disease is now recommended for newly detected type I diabetes along with other autoimmune conditions like thyroid disorders.